Analisis Faktor Risiko Kejadian Preeklampsia Pada Ibu Hamil Trimester III di Faskes Wilayah Kota Palangka Raya: Analysis of Risk Factors for Preeclampsia in Pregnant Women in the Third Trimester at Health Facilities in the City of Palangka Raya - Hatini, Erina Eka; Elytha Rahmawati; Irene Febriani; Yeni Lucin (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2025)
Preeclampsia is an increase in blood pressure that occurs after 20 weeks of pregnancy. Preeclampsia is the main cause of maternal death. Case control study with a retrospective approach. The sample consisted of 90 people divided into 45 cases and 45 controls. Using the chi square test. The results showed that there was a relationship between age > 35 years and the incidence of preeclampsia (p-value= 0.002 OR=4.571), parity and the incidence of preeclampsia (p-value= 0.039) OR=2.923, history of preeclampsia and the incidence of preeclampsia (p-value= 0.000), family history of preeclampsia with preeclampsia (p-value= 0.000) OR=6.089, obesity with preeclampsia (p-value= 0.000) OR=5.474, diabetes with preeclampsia (p-value= 0.039) OR= 4.529 , chronic hypertension with the incidence of preeclampsia (p-value= 0.000), MAP with the incidence of preeclampsia (p-value= 0.000), urine protein with the incidence of preeclampsia (p-value= 0.000), while there is no relationship between pregnancy with assisted technology and the incidence preeclampsia (p-value= 0.494), pregnancy interval > 10 years with the incidence of preeclampsia (p-value= 0.361) OR= 4,293, multiple pregnancies with the incidence of preeclampsia (p-value= 0.616) OR= 3,143, kidney disease with the incidence of preeclampsia ( p-value= 1.000) OR= 2.047. This study shows that risk factors related to the incidence of preeclampsia are age, parity, history of preeclampsia, family history of preeclampsia, obesity, diabetes, chronic hypertension, MAP, and urine protein, while those that are not related are pregnancy with assisted technology, kidney disease, spacing of pregnancies, and multiple pregnancies.